Therapeutic Genome Editing in Cardiovascular Diseases - Nishiga, Masataka (Adv Drug Deliv Rev, 2020)
During the past decade, developments in genome editing technology have fundamentally transformed biomedical research. In particular, the CRISPR/Cas9 system has been extensively applied because of its simplicity and ability to alter genomic sequences within living organisms, and an ever increasing number of CRISPR/Cas9-based molecular tools are being developed for a wide variety of applications. While genome editing tools have been used for many aspects of biological research, they also have enormous potential to be used for genome editing therapy to treat a broad range of diseases. For some hematopoietic diseases, clinical trials of therapeutic genome editing with CRISPR/Cas9 are already starting phase I. In the cardiovascular field, genome editing tools have been utilized to understand the mechanisms of diseases such as cardiomyopathy, arrythmia, and lipid metabolism, which now open the door to therapeutic genome editing. Currently, therapeutic genome editing in the cardiovascular field is centered on liver-targeting strategies to reduce cardiovascular risks. Targeting the heart is more challenging. In this review, we discuss the potential applications, recent advances, and current limitations of therapeutic genome editing in the cardiovascular field.